INOVASI PEMANFAATAN DAGING BUAH PALA MENJADI PRODUK PANGAN FUNGSIONAL DI DESA LILIBOOI, KECAMATAN LEIHITU BARAT, KABUPATEN MALUKU TENGAH - Grace Sipahelut, Sophia (HIRONO : Jurnal Pengabdian Masyarakat, 2025)
Lilibooi Village is known as one of the main centers of nutmeg production in Central Maluku Regency. Until now, nutmeg has generally been traded in the form of seeds and mace, while the flesh of the fruit is rarely utilized, even though it still contains various nutrients and has functional properties. Based on this potential availability and functional value, a Community Service (PkM) activity was carried out with the aim of empowering Lilibooi Village residents by increasing their knowledge and skills in processing nutmeg into a functional product in the form of velva. This program was attended by 20 participants and implemented through counseling and evaluation methods. The material provided covered the nutritional content and functional properties of nutmeg flesh as well as the stages of making nutmeg velva. The evaluation results showed that this activity was able to increase community knowledge and understanding regarding the innovative use of nutmeg flesh as a functional food product in the form of velva.